The diagnosis and comparison of physical abilities of skiers and footballers - Vasilios Giovanis; Panagiotis Vasileiou; Evangelos Bekris (H.S. Skovoroda Kharkov National Pedagogical University, 2017)
Purpose: The purpose of this research was to diagnose the physical abilities such as speed, strength, agility and endurance of alpine skiers and footballers through the same country tests. Also, the purpose was to compare the performance and test results of the above tested against one another. Methods: The sample of 58 individuals came from two groups of men of different sports: skiing (n = 29) aged 18-26 (20.97 ± 2.08 years) and football (n = 29) aged 18-25 (21, 28 ± 1.56 years), while the level in each group was the advanced and the beginner respectively. Until the trials, the ski and football teams had a training program exercising physical abilities and skills three days a week for the specialties and one day a week the select skiing session and the compulsory football session according to the curriculum. In order to diagnose and compare the physical abilities of ski students and football students, the following four tests of Alpine skiing on dry ground were used after the ski season on this day in April 2014: A) Route speed test (route 20m with flight start). B) Explosive power tests of the lower limbs (eightfold with alternating tossing of feet). C) Agility Tests (Slalom's track on a "folder" 5m x 5m). D) Anaerobic test (jumping obstacle 20cm height for 60sec). Results: In the skiing specialty we have a great correlation between speed tests and other physical abilities and agility with endurance (r = -0,72). In football specialty there was a great correlation between speed and power tests (r = - 0.65) and agility with the power (r = - 0.69). In optional skiing, we have a moderate correlation between the tests, while in the A year football students the correlation between speed and strength (r = - 0.81) is distinguished. Conclusions: It is noteworthy that the students of the first year of football as well as the specialists do not have as good results in endurance as compared to the students of the skiing, even though the football game lasts 90 minutes compared to Alpine skiing 1-2 minutes.